1988
DOI: 10.1098/rstb.1988.0022
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentary record of climatic variation in the southern North Sea

Abstract: The sedimentary sequence on the shelf of the southern North Sea records Quaternary climatic changes in two ways. They are indicated directly by moraine and glaciofluvial deposits from the Elsterian, Saalian and Weichselian glacial periods when the British and the Scandinavian ice sheets covered parts of the area. An indirect response to the climate is indicated by sea-level changes. Phases of cooling are characterized by regressions and low sea-level stands; phases of warming are indicated by marine transgress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…14). It is based on data reviewed by Rozycki (1972), Liedtke (1975), Bowen et al (1986), Eissmann (1986), Houmark-Nielsen (1987, McCabe (1987), Long et al (1988), Petersen and Kronborg (1991) and Kozarski (1992). The LGM corresponds with the Jylland phase (Main Stationary Line) in Denmark, the Brandenburg phase in Germany, the Leszno phase in Poland, the South Irish End Moraine in Ireland and the Dimlington phase in the UK.…”
Section: This Issue)mentioning
confidence: 99%
“…14). It is based on data reviewed by Rozycki (1972), Liedtke (1975), Bowen et al (1986), Eissmann (1986), Houmark-Nielsen (1987, McCabe (1987), Long et al (1988), Petersen and Kronborg (1991) and Kozarski (1992). The LGM corresponds with the Jylland phase (Main Stationary Line) in Denmark, the Brandenburg phase in Germany, the Leszno phase in Poland, the South Irish End Moraine in Ireland and the Dimlington phase in the UK.…”
Section: This Issue)mentioning
confidence: 99%
“…This formation is of glacilacustrine and glacimarine origin and thought to record the advance of the British Ice Sheet during the late Devensian (Cameron et al, 1987;Long et al, 1988). Glacial deposition during the LGM is thought to be represented by the Cape Shore, Coal Pit and Bolders Bank Formations.…”
Section: North Sea Offshore Evidencementioning
confidence: 99%
“…This supports the reconstruction of Ehlers and Wingfield (1991) for the southernmost part of the North Sea based upon the distribution of Dimlington Stadial tunnel valleys but questions their restricted ice limits proposed further north based on the Wee Bankie Formation (cf. Long et al, 1988).…”
Section: North Sea Offshore Evidencementioning
confidence: 99%
“…To the south, within the Dutch sector, Beets et al (2005) have identified a MIS 8 till based upon AAR dating of mollusc shells and foraminifera tests although previously this till was attributed to the younger 'Saalian' (MIS 6) glaciation (Ehlers, 1990;Carr, 2004). The precise configuration of the Scandinavian and British ice sheets in the North Sea during the Saalian has been debated extensively (Long et al, 1988;Rappol et al, 1989;Laban, 1995;Carr, 2004). In the Southern North Sea, the presence of the Cleaver Bank Formation suggests that ice-free glaciolacustrine conditions prevailed across much of the region at this time (Rappol et al, 1989;Cameron et al, 1992;Laban, 1995;Busschers et al, 2008;Davies et al, 2012).…”
mentioning
confidence: 99%